After the Ottomans (London ; New York)
vi, 295 sayfa
Keywords: “This book deals with the lasting impact and the formative legacy of removal, dispossession and the politics of genocide in the last decade of the Ottoman Empire. For understanding contemporary Turkey and the neighboring region, it is important to revisit the massive transformation of the late-Ottoman world caused by persistent warfare between 1912 and 1922. This fourth volume of a series focusing on the Ottoman Cataclysm looks at the century-long consequences and persistent implications of the Armenian genocide. It deals with the actions and words of the Armenians as they grappled with total destruction and tried to emerge from under it. Eleven scholars of history, anthropology, literature and political science explore the Ottoman Armenians not only as the major victims of the First World War and the post-war treaties, but also as agents striving for survival, writing history, transmitting the memory and searching for justice.” --